A Novel Antifungal System With Potential for Prolonged Delivery of Histatin 5 to Limit Growth of Candida albicans - Zambom, Carolina R.; da Fonseca, Fauller H.; Crusca, Edson; da Silva, Patrícia B.; Pavan, Fernando R.; Chorilli, Marlus; Garrido, Saulo S. (Frontiers in Microbiology, 2019)
Currently 75-88% of fungal infections are caused by Candida species and Candida albicans is the main microorganism that causes these infections, especially oral candidiasis. An option for treatment involves the use of the antifungal peptide Histatin 5 (Hst 5), which is naturally found in human saliva but which undergoes rapid degradation when present in the oral cavity. For this reason, it is important to develop a way of applying this peptide to the oral lesions, which promotes the gradual release of the peptide. In the present study we have evaluated the development of liposomes of different lipid compositions, loaded with the peptide as a way to promote its release slowly and gradually, preserving its antifungal potential. For this, the peptide 0WHistatin 5, an analog of the peptide Hst 5, was synthesized, which contains the amino acid tryptophan in its sequence. The solid phase synthesis method was used, followed by cleavage and purification. The liposomes were produced by thin film hydration technique in 3 different lipid compositions, F1, F2 and F3 and were submitted to an extrusion and sonication process to standardize the size and study the best technique for their production. The liposomes were characterized by dynamic light scattering, and tests were performed to determine the encapsulation efficiency, release kinetics, stability and evaluation of antifungal activity. The extruded liposomes presented average size in the range of 100 nm, while sonicated liposomes presented a smaller size in the range of 80 nm. The encapsulation efficiency was higher for the sonicated liposomes, being 34.5% for F1. The sonicated F3, presented better stability when stored for 60 days at 4 °C. The liposomes showed the ability to release the peptide for 96 hours, with the first peak after 5 hours, and a further increase of the released after 30 hours. Time-kill assay showed that the liposomes were able to control yeast growth for 72 hours. The data suggest that the liposomes loaded with 0WHistatin 5 maintained the action of the peptide and were able to limit the growth of C. albicans, being a suitable system for use in the treatment of oral candidiasis.